Local tumour progression after percutaneous ablation of colorectal liver metastases according to RAS mutation status. Issue 6 (27th February 2017) - Odisio, B. C.; Yamashita, S.; Huang, S. Y.; Harmoush, S.; Kopetz, S. E.; Ahrar, K.; Shin Chun, Y.; Conrad, C.; Aloia, T. A.; Gupta, S.; Hicks, M. E.; Vauthey, J.‐N.
Abstract: Background: Percutaneous ablation is a common treatment for colorectal liver metastasis (CLM). However, the effect of rat sarcoma viral oncogene homologue ( RAS ) mutation on outcome after ablation of CLMs is unclear. Methods: Patients who underwent image‐guided percutaneous ablation of CLMs from 2004 to 2015 and had known RAS mutation status were analysed. Patients were evaluated for local tumour progression as observed on imaging of CLMs treated with ablation. Multivariable Cox regression analysis was performed to determine factors associated with local tumour progression‐free survival. Results: The study included 92 patients who underwent ablation of 137 CLMs. Thirty‐six patients (39 per cent) had mutant RAS . Rates of local tumour progression were 14 per cent (8 of 56) for patients with wild‐type RAS and 39 per cent (14 of 36) for patients with mutant RAS ( P = 0·007). The actuarial 3‐year local tumour progression‐free survival rate after percutaneous ablation was worse in patients with mutant RAS than in those with wild‐type RAS (35 versus 71 per cent respectively; P = 0·001). In multivariable analysis, negative predictors of local tumour progression‐free survival werea minimum ablation margin of less than 5 mm (hazard ratio (HR) 2·48, 95 per cent c.i. 1·31 to 4·72; P = 0·006) and mutant RAS (HR 3·01, 1·60 to 5·77; P = 0·001). Conclusion: Mutant RAS is associated with an earlier and higher rate of local tumour progression in patients undergoing ablation of CLMs. Abstract : Mutant RAS poor prognostic factor